Battery cell and secondary battery
By setting up a lithium supplement layer on the separator and controlling the relationship between the holes and particle size, the problem of active lithium loss of silicon carbon negative electrode materials in lithium-ion batteries is solved, and a battery with high energy density and good circulation performance is achieved, reducing battery temperature rise and safety risks.
Patent Information
- Application Number
- CN202510611355.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-12
- Publication Date
- 2025-08-15
AI Technical Summary
Among the existing lithium-ion batteries, the silicon carbon negative electrode material has a large loss of active lithium during the first charge and discharge process, resulting in low energy density and poor circulation performance. The traditional lithium supplementation method has poor effect.
A lithium supplement layer is provided on the side of the diaphragm facing the positive electrode sheet. By controlling the relationship between the pore size of the hole and the particle size of the ternary active material, efficient lithium supplementation is achieved. After the first transformation, suitable pores are formed, electrolyte is stored, and lithium ion reception rate of the positive electrode active layer is improved, and interface polarization and side reactions are reduced.
It improves the energy density and circulation performance of the secondary battery, reduces the discharge temperature rise, and improves the safety and circulation life of the battery.
Smart Images

Figure CN120497486A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a battery cell and a secondary battery. Background Art
[0002] Lithium-ion batteries, with their high specific energy, high operating voltage, low self-discharge rate, compact size, and light weight, are widely used in consumer electronics. With the rapid development of electric vehicles and mobile electronic devices, demands for lithium-ion batteries' energy density, safety, and cycle performance are becoming increasingly stringent.
[0003] Commonly used negative electrode materials in existing lithium-ion batteries include silicon-carbon negative electrode materials, silicon-oxygen-carbon negative electrode materials, and silicon-oxygen negative electrode materials. Silicon-carbon negative electrode materials are widely used in lithium-ion batteries due to their high specific capacity and other properties. However, silicon-carbon negative electrode materials have low initial efficiency, resulting in large losses of active lithium during the first charge and discharge process and low battery energy density. The traditional method of lithium replenishment is to directly add the lithium replenisher to the positive electrode slurry, but the lithium replenishment effect has not met expectations, and the energy density and cycle life of lithium-ion batteries need to be further improved.
[0004] Therefore, there is an urgent need to develop a battery cell with higher energy density and longer cycle life. Summary of the Invention
[0005] The present invention provides a battery core having high energy density and good cycle performance.
[0006] The present invention provides a secondary battery. Since the secondary battery includes the above-mentioned battery core, the secondary battery has higher energy density and better cycle performance.
[0007] The present invention provides a battery cell, comprising a stacked positive electrode sheet, a separator, and a negative electrode sheet; the positive electrode sheet comprises a positive electrode active layer, the positive electrode active layer comprising single crystal particles of a ternary active material and polycrystalline particles of a ternary active material; the separator comprises a separator substrate and a lithium replenishing layer, the lithium replenishing layer being arranged on at least a portion of the surface of the separator substrate facing the positive electrode sheet; the lithium replenishing layer forms pores after initial formation; the battery cell satisfies Formula 1,
[0008] 0.5r≤v≤2R Formula 1
[0009] In Formula 1, v is the pore size, μm; r is the average particle size of the single crystal particles of the ternary active material, μm; and R is the average particle size of the polycrystalline particles of the ternary active material, μm.
[0010] In the battery cell as described above, the negative electrode sheet includes a negative electrode active layer, and the negative electrode active layer includes a silicon-carbon material.
[0011] The battery cell as described above, wherein the battery cell satisfies Formula 2,
[0012] X=a×54+b×5 Formula 2
[0013] In Formula 2, a is the silicon content in the negative electrode active layer, %; b is the carbon content in the negative electrode active layer, %; and X is the thickness of the lithium replenishing layer, μm.
[0014] The battery cell as described above, wherein 5%≤a≤50%; and / or, 40%≤b≤80%; and / or, 5≤X≤30μm.
[0015] In the battery cell as described above, the average particle size of the single crystal particles of the ternary active material is 2 to 5 μm; and / or the average particle size of the polycrystalline particles of the ternary active material is 6 to 15 μm.
[0016] The battery cell as described above, wherein the lithium replenishing layer comprises an organic lithium replenishing agent and a conductive agent, and the conductive agent comprises carbon nanotubes;
[0017] Preferably, the lithium replenishing layer comprises 70-80 parts of an organic lithium replenishing agent, 15-20 parts of a conductive agent, and 5-10 parts of a binder, in parts by weight.
[0018] The battery cell as described above, wherein the organic lithium supplement comprises at least one of lithium squarate, lithium oxalate, lithium acetate, and lithium benzoate;
[0019] And / or, the conductive agent further comprises carbon black; wherein the mass ratio of the carbon nanotubes to the carbon black is (10-20):(1-5).
[0020] The battery cell as described above, wherein the aspect ratio of the carbon nanotubes is 1000 to 10000;
[0021] And / or, the carbon nanotubes and the organic lithium supplement agent satisfy Formula 3,
[0022] 2C≤L≤16C Formula 3
[0023] In Formula 3, L is the length of the carbon nanotube, μm; C is the D50 of the organic lithium supplement, μm.
[0024] In the battery cell as described above, the positive electrode sheet, the separator and the negative electrode sheet are sequentially stacked and wound to form an arc region and flat regions on both sides of the arc region, and the lithium replenishing layer is provided on the surface of the separator substrate corresponding to the flat region.
[0025] Preferably, the surface of the diaphragm substrate corresponding to the plane area includes N blank areas and M coating areas, and the lithium replenishing layer is provided in the coating areas; wherein N≥1 and M≥1.
[0026] The present invention also provides a secondary battery comprising the above-mentioned battery cell.
[0027] The present invention replenishes lithium for the positive electrode by arranging a lithium replenishing layer on the side of the separator facing the positive electrode sheet; after the lithium replenishing layer is initially formed, holes are generated, and the relationship between the pore size of the holes and the average particle size of the ternary active material single crystal particles and the ternary active material polycrystalline particles in the positive electrode active layer is limited, thereby reducing the interface polarization and interface side reactions between the positive electrode side and the separator, reducing the temperature rise of the discharged battery, and further improving the energy density and cycle performance of the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0029] Figure 1 This is a schematic structural diagram of the diaphragm provided in Example 1 of the present invention;
[0030] Figure 2 This is a schematic structural diagram of the battery cell provided in Example 1 of the present invention;
[0031] Figure 3 Schematic diagram of coating the lithium replenishing layer provided in Example 1 of the present invention on the separator; (a) horizontal stripe coating; (b) vertical stripe coating; (c) circular stripe coating; (d) irregular coating;
[0032] Figure 4 Schematic diagram of the coating area of the lithium replenishing layer provided in Example 1 of the present invention;
[0033] Figure 5 This is a SEM image of the lithium replenishing layer provided in Example 1 of the present invention;
[0034] Figure 6 This is an EDS layered image of the lithium supplement layer provided in Example 1 of the present invention;
[0035] Figure 7 This is an EDS elemental analysis diagram of the surface of the lithium supplement layer provided in Example 1 of the present invention;
[0036] Figure 8 This is a cross-sectional SEM image of the lithium supplement layer provided in Example 1 of the present invention;
[0037] Figure 9 This is a SEM image of the cross-sectional CNT distribution of the lithium replenishment layer provided in Example 1 of the present invention;
[0038] Figure 10(a) SEM image of the cross section of the lithium replenishment layer provided in Example 1 of the present invention; (b) EDS layered image; (c) EDS surface scan distribution map of aluminum elements; (d) EDS elemental analysis map.
[0039] Reference numerals:
[0040] 1-diaphragm substrate; 2-glue layer; 3-ceramic layer; 4-lithium replenishing layer; 5-planar area; 6-arc area.
[0041] The above drawings illustrate specific embodiments of the present application, which will be described in more detail below. These drawings and the textual description are not intended to limit the scope of the present application in any way, but rather to illustrate the concepts of the present application to those skilled in the art by reference to specific embodiments. DETAILED DESCRIPTION
[0042] To make the objectives, technical solutions, and advantages of the present invention more clear, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts shall fall within the scope of protection of the present invention.
[0043] Existing secondary batteries experience significant loss of active lithium during the initial charge and discharge process, and the SEI (Separate Electron Interphase) formation at the silicon-carbon negative electrode continues to consume active lithium during cycling, leading to rapid capacity decay. This results in low energy density and poor cycling performance in existing high-silicon battery systems. Therefore, lithium replenishment is necessary for secondary batteries. Traditionally, lithium replenishment involves directly adding an organic lithium replenisher to the positive electrode slurry. However, the effectiveness of this method of replenishing lithium needs to be further improved.
[0044] The inventors discovered that the reason why the lithium replenishment effect is not good when the organic lithium replenisher is directly added to the positive electrode slurry is that the organic lithium replenisher is difficult to disperse in the positive electrode slurry, resulting in local lithium content being too high or too low. In particular, when the lithium content is too high, the organic lithium replenisher is difficult to completely decompose during the initial formation. During subsequent battery cycles, the remaining organic lithium replenisher will continue to decompose, causing battery bulging and affecting battery performance. In addition, the decomposition of the organic lithium replenisher causes pores to form in the positive electrode sheet, increasing internal resistance, reducing conductivity, and affecting battery performance. The accumulation of pores causes the electrode sheet structure to be destroyed, reducing cycle performance.
[0045] The inventors attempted to overcome the difficulty of dispersing the organic lithium replenisher in the positive electrode slurry by placing the lithium replenisher layer on the separator, facing the side of the positive electrode. However, they found that even after the initial formation, placing the lithium replenisher layer on the separator still had limited lithium replenishment effect on the positive electrode. The inventors analyzed that this may be due to the limited lithium ion acceptance capacity of the positive electrode active layer, which prevented efficient lithium replenishment.
[0046] Based on this, Figure 2 As shown, the present invention provides a battery cell, comprising a stacked positive electrode sheet, a separator, and a negative electrode sheet; the positive electrode sheet comprises a positive electrode active layer, the positive electrode active layer comprises single crystal particles of a ternary active material and polycrystalline particles of a ternary active material; the separator comprises a separator substrate and a lithium replenishing layer, the lithium replenishing layer being arranged on at least a portion of the surface of the separator substrate facing the positive electrode sheet; the lithium replenishing layer forms pores after the initial formation; the battery cell satisfies Formula 1,
[0047] 0.5r≤v≤2R Formula 1
[0048] In formula 1, v is the pore diameter, μm; r is the average particle size of the single crystal particles of the ternary active material, μm; and R is the average particle size of the polycrystalline particles of the ternary active material, μm.
[0049] Specifically, the positive electrode sheet of the present invention includes a positive electrode current collector and a positive electrode active layer arranged on at least a portion of the surface of the positive electrode current collector, the positive electrode active layer includes a ternary active material; wherein the ternary active material includes ternary active material single crystal particles and ternary active material polycrystalline particles; the diaphragm includes a diaphragm matrix and a lithium replenishing layer located on the surface of the diaphragm matrix, the lithium replenishing layer faces the positive electrode active layer of the positive electrode sheet, and the lithium replenishing layer includes a lithium replenishing agent.
[0050] The battery cell of the present invention has a high energy density and good cycle performance. The reason is that: on the one hand, during the formation process of the battery, when the pore size of the pores, the particle size of the single crystal particles of the ternary active material and the particle size of the polycrystalline particles of the ternary active material meet the above-mentioned relationship, the electrolyte with an appropriate content stored in the pores can efficiently match the number of active lithium ions released by the lithium replenisher and the lithium insertion sites of the positive electrode active layer, thereby improving the acceptance rate of the positive electrode active layer for active lithium ions, allowing more lithium ions to be embedded in the positive electrode active layer, thereby achieving precise lithium replenishment and eliminating the safety hazards that may be caused by excessive lithium replenishment; on the other hand, the lithium replenisher decomposes to release active lithium ions, and pores are formed in the lithium replenishment layer. The pores can improve the wettability and liquid retention capacity of the diaphragm, reduce the interface polarization and interface side reactions between the positive electrode side and the diaphragm, reduce the battery temperature rise during discharge, especially the battery temperature rise during high-rate discharge, which is conducive to further improving the energy density and cycle performance of the battery.
[0051] The present invention does not specifically limit the structure of the positive electrode sheet. In one embodiment, in addition to the ternary active material, the positive electrode active layer further includes a conductive agent and a binder.
[0052] The present invention does not specifically limit the type of ternary active material, and it can be any conventional material in the art. For example, the ternary active material can be any one of a nickel-cobalt-manganese ternary material and a nickel-cobalt-aluminum ternary material.
[0053] The present invention does not further limit the content of each metal in the ternary active material, whether other doping metals are included, and the content of the doping metals, and conventional proportions in the art can be used.
[0054] The present invention does not specifically limit the material of the positive electrode current collector in the positive electrode sheet, and can be any conventional material in the art. For example, the material of the positive electrode current collector can be any one of aluminum foil and nickel foil.
[0055] The present invention does not specifically limit the type of conductive agent in the positive electrode active layer, and can be any conventional material in the art. For example, the conductive agent can be selected from at least one of carbon black, acetylene black, graphene, Ketjen black, and carbon fiber.
[0056] The present invention does not specifically limit the type of binder in the positive electrode active layer, and can be any conventional material in the art. For example, the binder can be selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, and polyurethane.
[0057] The present invention does not specifically limit the preparation method of the positive electrode sheet. In one embodiment, the positive electrode sheet can be prepared by a method comprising the following steps:
[0058] The positive electrode active material (ternary active material) of the present invention is dispersed with a conductive agent and a binder in an N-methylpyrrolidone (NMP) solvent, and the mixture is fully stirred and mixed to form a uniform positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector, and the positive electrode sheet is obtained after drying, rolling and slitting.
[0059] The present invention does not impose any specific restrictions on the amounts of the positive electrode active material, the conductive agent, and the binder, which can be adjusted according to actual conditions.
[0060] The present invention does not specifically limit the structure of the negative electrode sheet. In one embodiment, the negative electrode sheet specifically includes a negative electrode current collector and a negative electrode active layer formed of a negative electrode active material disposed on the surface of the negative electrode current collector. The negative electrode active layer includes the negative electrode active material, a binder, and a conductive agent.
[0061] The present invention does not specifically limit the material of the negative electrode current collector, and it can be any conventional material in the art. For example, the negative electrode current collector can be any one of copper foil, nickel foam, and copper foam.
[0062] The present invention is not strictly limited to the negative electrode active material in the negative electrode sheet, and can be at least one of the negative electrode active materials commonly used in lithium-ion batteries, such as graphite, hard carbon, soft carbon, mesophase carbon microbeads, silicon-based negative electrode materials (mainly including silicon oxide, silicon-carbon negative electrode), tin-based negative electrode materials (mainly including tin, tin alloy), etc.
[0063] The present invention does not specifically limit the type of binder in the negative electrode active layer, and the binder may be any binder commonly used in current battery negative electrodes. For example, the binder may be selected from at least one of carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyvinyl alcohol, and sodium polyacrylate.
[0064] The present invention does not specifically limit the type of conductive agent in the negative electrode active layer; it can be any conductive agent commonly used in battery negative electrodes. For example, the conductive agent can be selected from at least one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, and graphene.
[0065] The present invention does not specifically limit the preparation method of the negative electrode sheet. In one embodiment, the negative electrode sheet can be prepared by a method comprising the following steps:
[0066] The negative electrode active material, conductive agent and binder are dispersed in deionized water and fully stirred to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode collector, and the negative electrode sheet is obtained after drying, rolling and cutting.
[0067] The present invention does not impose any specific restrictions on the amounts of the negative electrode active material, the conductive agent, and the binder, which can be adjusted according to actual conditions.
[0068] The battery cell of the present invention further includes an electrolyte. The composition of the electrolyte is not specifically limited and may include one or more solvents commonly used in current battery electrolytes, as well as electrolyte lithium salts commonly used in current battery electrolytes. For example, the solvent may include at least one of ethylene carbonate, propylene carbonate, butylene carbonate, fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), diethyl carbonate (DEC), difluoroethylene carbonate (DFEC), dipropyl carbonate, ethyl methyl carbonate (EMC), ethyl acetate, ethyl propionate, propyl acetate, propyl propionate, sulfolane, and γ-butyrolactone; and the lithium salt may include at least one of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI).
[0069] Furthermore, a ceramic layer and a glue layer are included between the diaphragm substrate and the lithium supplement layer; Figure 1 As shown, the diaphragm includes, from bottom to top, a glue layer 2, a diaphragm substrate 1, a ceramic layer 3, a glue layer 2 and a lithium replenishing layer 4.
[0070] The present invention does not specifically limit the type of the diaphragm substrate 1, and conventional materials in the art can be used. For example, the diaphragm substrate 1 can be selected from any one of polypropylene diaphragm (PP), polyethylene diaphragm (PE), polypropylene / polyethylene double-layer composite film (PP / PE), polyimide electrospun diaphragm (PI), polypropylene / polyethylene / polypropylene three-layer composite film (PP / PE / PP), and cellulose non-woven fabric diaphragm.
[0071] The present invention does not specifically limit the raw materials of the ceramic layer 3, and conventional materials in the art can be used. In one embodiment, the raw materials of the ceramic layer 3 include inorganic particles, a dispersant, and a binder. The inorganic particles include at least one of aluminum oxide, magnesium oxide, boehmite, barium sulfate, barium titanate, zinc oxide, calcium oxide, and silicon dioxide. The dispersant includes at least one of polyethylene glycol, sodium dodecylbenzene sulfonate, sodium lauryl sulfate, sodium hexametaphosphate, and polyvinylpyrrolidone (PVP). The binder includes polyvinylidene fluoride.
[0072] The present invention does not impose any specific restrictions on the mass ratio of the raw materials in the ceramic layer 3 , and conventional mass ratios in the art may be used.
[0073] The present invention does not impose any specific limitation on the thickness of the ceramic layer 3, which can be adjusted according to actual conditions. In one embodiment, the thickness of the ceramic layer is 1 to 2 μm.
[0074] Illustratively, the thickness of the ceramic layer 3 is 1 μm, 1.2 μm, 1.3 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm or 2 μm, or a range consisting of any two of these values.
[0075] The present invention does not specifically limit the type of adhesive layer 2; conventional materials in the art may be used. In one embodiment, the adhesive layer 2 includes at least one of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer, sodium carboxymethyl cellulose, polymethyl methacrylate, polyacrylonitrile, styrene-butadiene rubber, polyvinyl alcohol, polyacrylamide, and an acrylate adhesive.
[0076] It should be noted that when the adhesive layer 2 is a mixture of the above substances, the present invention does not impose any specific limitation on the proportion of each specific substance in the mixture.
[0077] The present invention does not impose any specific limitation on the thickness of the adhesive layer 2, which can be adjusted according to actual conditions. In one embodiment, the thickness of the adhesive layer 2 is 1 to 2 μm.
[0078] Illustratively, the thickness of the adhesive layer 2 is 1 μm, 1.2 μm, 1.3 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm or 2 μm, or a range consisting of any two of these values.
[0079] The present invention does not further limit the sources of the ternary active material, the negative electrode active material, and the lithium supplement agent. Commercially available products or products prepared by conventional preparation methods familiar to those skilled in the art may be used.
[0080] In a specific embodiment, the negative electrode sheet includes a negative electrode active layer, and the negative electrode active layer includes a silicon-carbon material.
[0081] Specifically, the negative electrode sheet includes a negative electrode current collector and a negative electrode active layer disposed on at least a portion of the surface of the negative electrode current collector. The negative electrode active layer including silicon-carbon material helps to further improve the energy density of the battery.
[0082] In one embodiment, the battery cell satisfies Formula 2,
[0083] X=a×54+b×5 Formula 2
[0084] In Formula 2, a is the silicon content in the negative electrode active layer, %; b is the carbon content in the negative electrode active layer, %; and X is the thickness of the lithium replenishing layer, μm.
[0085] Because the initial SEI formation in secondary batteries consumes more active lithium, while graphite consumes relatively less active lithium when it first forms the SEI, the required amount of lithium replenishment is less. The present invention sets the thickness of the lithium replenishment layer based on the silicon and carbon content in the negative electrode active layer. When the thickness of the lithium replenishment layer satisfies the above relationship, it can meet the initial active lithium consumption requirements of the silicon-carbon negative electrode, significantly improving the battery energy density. It also achieves controllable lithium replenishment and avoids excessive residual lithium ions in the lithium replenisher.
[0086] In addition, the thickness of the lithium replenishment layer is set according to the above formula 2, which can reduce the shrinkage of the diaphragm at high temperature, further prevent direct contact between the positive and negative electrodes, and improve the furnace temperature performance; improve the wettability of the diaphragm to the electrolyte, promote lithium ion transmission, and further improve the cycle performance; the lithium replenishment layer provides an additional lithium ion transmission path, and the above thickness further reduces the interfacial impedance; and the thickness of the lithium replenishment layer satisfies the above relationship, which can increase the mechanical strength of the diaphragm, further reduce the risk of dendrite piercing, and reduce the risk of overcharging / mechanical abuse.
[0087] In a specific embodiment, 5%≤a≤50%. When the silicon content in the negative electrode active layer is within this range, the energy density of the battery cell is improved while ensuring the structural stability and conductivity of the negative electrode active layer.
[0088] In a specific embodiment, 40%≤b≤80%. When the carbon content in the negative electrode active layer is within this range, the cycle stability of the battery cell can be further improved.
[0089] In a specific embodiment, 5≤X≤30 μm. When the thickness of the lithium supplement layer is within this range, the volume energy density of the battery cell can be further improved.
[0090] The present invention limits the silicon content and carbon content in the silicon-carbon material. The lower the silicon content, the lower the consumption of the first lithium formation, thereby reducing the amount of lithium replenishment and further improving the energy density and cycle life of the battery.
[0091] In order to further reduce the temperature rise of the discharged battery and improve the cycle performance of the battery, the present invention controls the average particle size of the single crystal particles of the ternary active material and the average particle size of the polycrystalline particles of the ternary active material.
[0092] In one embodiment, the average particle size of the ternary active material single crystal particles is 2 to 5 μm. Within this range, the average particle size of the ternary active material single crystal particles can further shorten the lithium ion diffusion path, reduce internal resistance, and reduce heat generation.
[0093] Illustratively, the average particle size of the ternary active material single crystal particles is 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm, or a range consisting of any two of these values.
[0094] In a specific embodiment, the average particle size of the polycrystalline particles of the ternary active material is 6 to 15 μm. When the average particle size of the polycrystalline particles of the ternary active material is within this range, the structural stability can be further improved.
[0095] Exemplarily, the average particle size of the polycrystalline particles of the ternary active material is 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, 10.5 μm, 11 μm, 11.5 μm, 12 μm, 12.5 μm, 13 μm, 13.5 μm, 14 μm, 14.5 μm or 15 μm, or a range consisting of any two of these values.
[0096] When the average particle size of the single crystal particles of the ternary active material and the average particle size of the polycrystalline particles of the ternary active material simultaneously meet the above ranges, the lithium ion diffusion path can be further shortened, and the internal resistance and temperature rise can be reduced.
[0097] In order to further improve the lithium replenishment effect, the present invention also defines the composition of the lithium replenishment layer. In detail, the lithium replenishment layer includes an organic lithium replenishing agent and a conductive agent, and the conductive agent includes carbon nanotubes. Among them, the carbon nanotubes (CNTs) of the present invention can promote the decomposition of the organic lithium replenishing agent. The carbon nanotubes form a conductive network in the lithium replenishing layer and in the pores generated after the decomposition of the organic lithium replenishing agent, which can effectively reduce the interfacial polarization between the positive electrode and the diaphragm, which is beneficial to reduce the temperature rise of rate discharge and improve the rate discharge performance. In addition, the addition of carbon nanotubes can reduce its decomposition potential, which is beneficial to the full decomposition of the organic lithium replenishing agent. Compared with inorganic lithium replenishing agents, organic lithium replenishing agents have higher specific capacity, can provide more lithium ions, and further improve the energy density of the battery; they also have better electrochemical stability, which further improves the cycle life and safety of the battery.
[0098] Furthermore, the lithium replenishing layer comprises 70-80 parts of an organic lithium replenishing agent, 15-20 parts of a conductive agent, and 5-10 parts of a binder, by weight. This ratio can further enhance the lithium replenishing effect of the lithium replenishing layer and maintain a long-lasting adhesive force.
[0099] In one embodiment, the organic lithium supplement includes at least one of lithium squarate, lithium oxalate, lithium acetate, and lithium benzoate. These organic lithium supplements are gas-releasing lithium supplements. After the initial charge, the organic lithium supplement releases active lithium, thereby replenishing the positive electrode.
[0100] In one embodiment, the binder of the lithium replenishing layer includes at least one of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer, sodium carboxymethyl cellulose, polymethyl methacrylate, polyacrylonitrile, styrene-butadiene rubber, polyvinyl alcohol, polyacrylamide and acrylic ester binders.
[0101] In one embodiment, the conductive agent further comprises carbon black, wherein the mass ratio of carbon nanotubes to carbon black is (10-20):(1-5). When the conductive agent comprises carbon black and carbon nanotubes in this mass ratio, the conductive network formed by the conductive agent combines the advantages of a one-dimensional structure (carbon black) and a two-dimensional structure (carbon nanotubes), making the formed conductive network structure more compact and further improving the conductivity of the conductive agent.
[0102] Illustratively, the mass ratio of carbon nanotubes to carbon black is 10:1, 11:1.5, 12:2, 13:2.5, 14:3, 15:3.5, 16:4, 17:4.5, 18:5, 19:5, 20:1 or 20:5, or a range consisting of any two values therein.
[0103] Furthermore, in order to enable the carbon nanotubes to better support the pores, the aspect ratio of the carbon nanotubes is controlled.
[0104] In a specific embodiment, the aspect ratio of the carbon nanotubes is 1000 to 10000. Within this range, the carbon nanotubes can better support the pores and enhance the stability of the pores.
[0105] Illustratively, the aspect ratio of the carbon nanotubes is 1000, 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000 or 10000, or a range consisting of any two of these values.
[0106] In one embodiment, the carbon nanotubes and the organic lithium supplement satisfy Formula 3:
[0107] 2C≤L≤16C Formula 3
[0108] In formula 3, L is the length of the carbon nanotube, μm; C is the D50 of the organic lithium supplement, μm.
[0109] When the length of the carbon nanotubes and the D50 of the organic lithium replenisher meet the above relationship, the lithium replenishment layer during and after the first charge formation is similar to a 3D sponge layer. The carbon nanotubes can better support the holes, so that the holes can still be maintained during the cycle, and can reserve expansion buffer space for silicon-doped batteries, thereby effectively solving the problems of deformation and fragmentation during the formation and cycling of silicon-based system batteries, thereby improving the battery's cycle performance.
[0110] Illustratively, the length of the carbon nanotubes is 2 times the D50 of the organic lithium supplement agent, the length of the carbon nanotubes is 4 times the D50 of the organic lithium supplement agent, the length of the carbon nanotubes is 6 times the D50 of the organic lithium supplement agent, the length of the carbon nanotubes is 8 times the D50 of the organic lithium supplement agent, the length of the carbon nanotubes is 10 times the D50 of the organic lithium supplement agent, the length of the carbon nanotubes is 12 times the D50 of the organic lithium supplement agent, the length of the carbon nanotubes is 14 times the D50 of the organic lithium supplement agent, or the length of the carbon nanotubes is 16 times the D50 of the organic lithium supplement agent, or a range consisting of any two of these values.
[0111] In order to achieve regionally controllable lithium replenishment and further reduce the probability of lithium deposition at the arc of the negative electrode, the present invention also controls the coating area of the lithium replenishment layer.
[0112] like Figure 2 As shown, in a specific embodiment, the battery cell of the present invention includes a positive electrode sheet, a separator and a negative electrode sheet stacked and wound in sequence to form an arc area 6 and a flat area 5 located on both sides of the arc area 6, and the lithium replenishing layer is arranged on the surface of the separator substrate corresponding to the flat area 5.
[0113] Typically, because the arc-shaped area of a wound cell has a smaller capacity balance CB value than the overall battery, the negative electrode arc area cannot accommodate excess active lithium, leading to arc-shaped lithium deposition. However, the present invention places the lithium replenishment layer in the flat area, effectively avoiding the arc-shaped area. This improves the lithium deposition window of the battery after lithium replenishment.
[0114] In one embodiment, the surface of the diaphragm substrate 1 corresponding to the plane area 5 includes N blank areas and M coating areas, and the lithium replenishing layer is provided in the coating area; N≥1, M≥1.
[0115] The blank area is the directly exposed diaphragm substrate, without any functional layer applied. The coated area is the area used for applying the lithium replenishment layer. The present invention does not limit the number of blank and coated areas, nor their positional relationship. By placing the lithium replenishment layer only in the coated area, the interfacial adhesion between the positive electrode and the diaphragm is improved while ensuring lithium replenishment, further enhancing the electrochemical performance and mechanical stability of the battery cell.
[0116] like Figure 3 As shown, the present invention does not specifically limit the shapes of the coated area and the uncoated area, including but not limited to horizontal stripe coating (a), vertical stripe coating (b), circular stripe coating (c), and irregular coating (d).
[0117] The present invention does not impose any specific restrictions on the coating area of the lithium supplement layer on the diaphragm, and can be adjusted according to actual conditions. Figure 4 As shown, taking the longitudinal stripes as an example, the plane area includes coated areas and uncoated areas that are spaced apart. The width of the coated areas is W1, and each W1 can be the same or different; the width of the uncoated areas is W2, and each W2 can be the same or different.
[0118] In one embodiment, W1 = (1-10) W2.
[0119] Illustratively, W1=1W2, W1=2W2, W1=3W2, W1=4W2, W1=5W2, W1=6W2, W1=7W2, W1=8W2, W1=9W2 or W1=10W2, or a range consisting of any two of these values.
[0120] The second aspect of the present invention provides a secondary battery comprising the above-mentioned battery cell, so that the secondary battery has a high energy density and good cycle performance.
[0121] The secondary battery of the present invention may be a lithium ion battery or a sodium ion battery.
[0122] The present invention does not specifically limit the method for preparing the secondary battery; conventional methods in the art may be employed. In one embodiment, the battery cells are encapsulated in pre-stamped aluminum-plastic film bags. After the encapsulated batteries are dried to remove moisture, the electrolyte is injected into the dried batteries. The batteries are then placed, formed, and resealed to complete the preparation of the lithium-ion battery.
[0123] The present invention is further described below through specific examples.
[0124] Example 1
[0125] The battery cell of this embodiment includes a stacked nickel-cobalt-manganese ternary active material positive electrode sheet, a separator and a silicon-carbon negative electrode sheet; the nickel-cobalt-manganese ternary active material positive electrode sheet, the separator and the silicon-carbon negative electrode sheet are stacked and wound in sequence to form a wound battery cell. The separator includes a separator substrate and a lithium replenishing layer arranged on the surface of the separator substrate, and the lithium replenishing layer faces the nickel-cobalt-manganese ternary active material positive electrode sheet. The battery cell includes an arc area and a plane area arranged at intervals, and the plane area is spaced apart with N coating areas. The lithium replenishing layer is located on the surface of the coating area and is striped coated, such as Figure 3 (b).
[0126] The nickel-cobalt-manganese ternary active material positive electrode sheet includes a positive electrode active layer, which, by weight, comprises 97.4% nickel-cobalt-manganese ternary active material, 1.6% carbon black as a conductive agent, and 1% polytetrafluoroethylene as a binder. The average particle size of the single-crystal particles of the nickel-cobalt-manganese ternary active material is 3μm, and the average particle size of the polycrystalline particles of the nickel-cobalt-manganese ternary active material is 7μm.
[0127] Silicon carbon material (average conductivity of 15S / cm, average particle size of 8μm), sodium carboxymethyl cellulose, polyacrylic acid, styrene-butadiene rubber, Super-P, and single-walled carbon nanotubes were mixed in a mass ratio of 90:1:2:2:1.5:3.5. An appropriate amount of water was added as a solvent. After stirring evenly with a vacuum mixer, the slurry was evenly coated on the surface of a high-strength carbon-coated copper foil with a thickness of 6μm. The single-sided surface density of the coating was 2.2mg / cm 2 The coated electrode was transferred to a vacuum drying oven and baked at 85°C for 12 hours. The electrode was then rolled and sliced using a double-roller press to obtain the negative electrode. The silicon content of the negative electrode active layer was 32% and the carbon content was 55%.
[0128] The lithium replenishment layer includes 70 parts of an organic lithium replenisher, lithium squarate, 20 parts of a conductive agent, and 10 parts of a binder, polyvinylidene fluoride. The conductive agent is a mixture of carbon nanotubes and carbon black, with a mass ratio of 10:1. The carbon nanotubes have an aspect ratio of 2000 and a length of 20 μm. The D50 value of the organic lithium replenisher, lithium squarate, is 3 μm. The above-described mixture of lithium squarate, carbon nanotubes, and carbon black, and polyvinylidene fluoride are mixed to prepare a slurry. The slurry is applied to the separator and dried to obtain a lithium replenishment layer with a thickness of 20 μm.
[0129] The battery cell is charged and discharged for the first time, and the pores formed in the lithium replenishment layer after the first formation have a pore diameter of 3μm.
[0130] Example 1-1
[0131] This embodiment is basically the same as embodiment 1, except that:
[0132] The single crystal particle size of the nickel-cobalt-manganese ternary active material is 2 μm, and the polycrystalline particle size of the nickel-cobalt-manganese ternary active material is 6 μm. The silicon content in the negative electrode active layer is 5% and the carbon content is 80%.
[0133] The lithium-replenishing layer comprises 75 parts of lithium oxalate (an organic lithium-replenishing agent), 18 parts of a conductive agent, and 7 parts of polyvinylidene fluoride (PVDF), a binder. The conductive agent is a mixture of carbon nanotubes and carbon black, with a mass ratio of 15:3. The carbon nanotubes have an aspect ratio of 5000.
[0134] The thickness of the lithium replenishing layer is 6.7 μm.
[0135] The battery cell is charged and discharged for the first time, and the pores formed in the lithium replenishment layer after the first formation have a diameter of 2μm.
[0136] Example 1-2
[0137] This embodiment is basically the same as embodiment 1, except that:
[0138] The single crystal particle size of the nickel-cobalt-manganese ternary active material is 5μm, and the polycrystalline particle size of the nickel-cobalt-manganese ternary active material is 15μm. The silicon content in the negative electrode active layer is 50% and the carbon content is 20%.
[0139] The lithium-replenishing layer comprises 80 parts of lithium oxalate (an organic lithium-replenishing agent), 15 parts of a conductive agent, and 5 parts of polyvinylidene fluoride (PVDF), a binder. The conductive agent is a mixture of carbon nanotubes and carbon black, with a mass ratio of 20:5. The carbon nanotubes have an aspect ratio of 10,000.
[0140] The thickness of the lithium replenishing layer is 28 μm.
[0141] The battery cell is charged and discharged for the first time, and the pores formed in the lithium replenishment layer after the first formation have a pore diameter of 4μm.
[0142] Example 2
[0143] This embodiment is basically the same as embodiment 1, except that:
[0144] The silicon content in the negative electrode active layer is 27% and the carbon content is 60%.
[0145] The thickness of the lithium replenishment layer is 17.6 μm.
[0146] Example 3
[0147] This embodiment is basically the same as embodiment 1, except that:
[0148] The silicon content in the negative electrode active layer is 24% and the carbon content is 63%.
[0149] The thickness of the lithium replenishment layer is 16.1 μm.
[0150] Example 4
[0151] This embodiment is basically the same as embodiment 1, except that:
[0152] The silicon content in the negative electrode active layer is 21% and the carbon content is 66%.
[0153] The thickness of the lithium replenishment layer is 14.6 μm.
[0154] Example 5
[0155] This embodiment is basically the same as embodiment 1, except that:
[0156] The silicon content in the negative electrode active layer is 2% and the carbon content is 75%.
[0157] The thickness of the lithium replenishing layer is 4.8 μm.
[0158] Example 5-1
[0159] This embodiment is basically the same as embodiment 1, except that:
[0160] The silicon content in the negative electrode active layer is 55% and the carbon content is 30%.
[0161] The thickness of the lithium replenishment layer is 31.2 μm.
[0162] Example 6
[0163] This embodiment is basically the same as embodiment 1, except that the average particle size of the nickel-cobalt-manganese ternary active material single crystal particles is 6 μm.
[0164] Example 6-1
[0165] This embodiment is basically the same as embodiment 1, except that the average particle size of the nickel-cobalt-manganese ternary active material single crystal particles is 1 μm.
[0166] Example 7
[0167] This embodiment is basically the same as embodiment 1, except that the average particle size of the polycrystalline particles of the nickel-cobalt-manganese ternary active material is 20 μm.
[0168] Example 7-1
[0169] This embodiment is basically the same as the embodiment 1, except that the average particle size of the polycrystalline particles of the nickel-cobalt-manganese ternary active material is 3 μm.
[0170] Example 8
[0171] This embodiment is basically the same as embodiment 1, except that the lithium replenishing layer includes 50 parts of an organic lithium replenishing agent.
[0172] Example 8-1
[0173] This embodiment is basically the same as embodiment 1, except that the lithium replenishing layer includes 90 parts of an organic lithium replenishing agent.
[0174] Example 8-2
[0175] This embodiment is basically the same as embodiment 1, except that the lithium replenishing layer includes 10 parts of a conductive agent.
[0176] Example 9
[0177] This embodiment is basically the same as embodiment 1, except that the mass ratio of carbon nanotubes to carbon black is 1:1.
[0178] Example 9-1
[0179] This embodiment is basically the same as embodiment 1, except that the mass ratio of carbon nanotubes to carbon black is 50:1.
[0180] Example 10
[0181] This embodiment is basically the same as embodiment 1, except that the aspect ratio of the carbon nanotubes is 500.
[0182] Example 10-1
[0183] This embodiment is basically the same as embodiment 1, except that the aspect ratio of the carbon nanotubes is 20,000.
[0184] Example 11
[0185] This embodiment is basically the same as embodiment 1, except that the length of the carbon nanotubes is 4 μm.
[0186] Example 11-1
[0187] This embodiment is basically the same as embodiment 1, except that the length of the carbon nanotubes is 60 μm.
[0188] Example 12
[0189] This embodiment is basically the same as embodiment 1, except that the conductive agent in the lithium replenishing layer is only carbon black.
[0190] Example 13
[0191] This embodiment is basically the same as embodiment 1, except that:
[0192] The entire planar area is coated with a lithium replenishing layer.
[0193] Comparative Example 1
[0194] The difference between this comparative example and Example 1 is:
[0195] The diaphragm only has a diaphragm matrix, no lithium replenishing layer, and no lithium replenishing agent is added to the positive electrode slurry.
[0196] Comparative Example 2
[0197] The difference between this comparative example and Example 1 is:
[0198] The pore diameter is 1 μm.
[0199] Comparative Example 3 (pore diameter is twice that of the polycrystalline particle size of the ternary active material)
[0200] The difference between this comparative example and Example 1 is:
[0201] The pore diameter is 15 μm.
[0202] Comparative Example 4 (No lithium supplement layer is applied to the diaphragm)
[0203] The difference between this comparative example and Example 1 is:
[0204] No lithium replenishing layer is coated on the diaphragm, and the organic lithium replenishing agent lithium squarate is directly added to the positive electrode slurry to prepare the positive electrode sheet; wherein, the mass ratio of the organic lithium replenishing agent lithium squarate is 1%, the positive electrode active material nickel-cobalt-manganese ternary active material is 96.4%, the conductive agent is 1.6%, and the binder polyvinylidene fluoride is 1%.
[0205] Test example
[0206] 1. The lithium supplement layer prepared in Example 1 was tested. The SEM image of the lithium supplement layer is shown in FIG. Figure 5 ,Depend on Figure 5 It can be seen that the CNTs in the slurry are fully wrapped on the surface of the lithium supplement particles after stirring; the EDS layered image of the lithium supplement layer is shown in Figure 6 ; The surface EDS element analysis diagram of the lithium supplement layer is shown in Figure 7 ,Depend on Figure 7 It can be seen that it mainly contains C, O, and F, and F comes from PVDF; the cross-sectional SEM image of the lithium supplement layer is shown in Figure 8 ; The cross-sectional SEM image of the CNT distribution of the lithium supplement layer is shown in Figure 9 ; The SEM image of the cross section of the lithium supplement layer is shown in Figure 10 (a) EDS layered image of the cross section of the lithium supplement layer is shown in Figure 10 (b) EDS surface scan distribution of aluminum elements in the cross section of the lithium supplement layer is shown in Figure 10 (c) EDS element analysis diagram of the cross section of the lithium supplement layer is shown in Figure 10 (d), by Figure 10 (d) shows that the ceramic layer is located between the base film and the lithium replenishment layer, and the position of the ceramic layer is determined by the distribution of aluminum elements.
[0207] 2. Secondary batteries were prepared using the cells obtained in the above examples and comparative examples, and the energy density and capacity retention rate after 600 cycles at 25°C of the secondary batteries were tested. The test results are shown in Table 1.
[0208] 1) Energy density detection method
[0209] Using a battery charge and discharge tester, the secondary battery prepared above was charged to 4.3V at 0.5C constant current at 25°C, then charged at constant voltage until the current dropped to 0.05C. After standing for 5 minutes, the battery was discharged to 2.5V at 0.5C constant current, and the first discharge capacity Q of the battery was recorded. 放 and the first discharge energy E 放 , weigh the battery mass as W, calculate the energy density ED = E 放 / W.
[0210] 2) Capacity retention rate detection method
[0211] The secondary battery prepared above was charged to 4.50V at a constant current of 1C at 25°C, then charged to 4.50V at a constant voltage of 0.05C, and then discharged to 3.0V at a discharge rate of 1C. This charge and discharge cycle was repeated 600 times. The discharge capacity Q1 at the first cycle and the discharge capacity Q at the 600th cycle were measured. 600 .
[0212] The capacity retention rate Q after 600 cycles is calculated according to the following formula:
[0213] Capacity retention rate Q = Q 600 / Q1×100%.
[0214] Table 1
[0215]
[0216]
[0217] It can be seen from Table 1 that, compared with the comparative example, the secondary battery prepared in the embodiment of the present invention has excellent energy density and cycle performance.
[0218] Finally, it should be noted that those skilled in the art will readily identify other embodiments of the present invention after considering the specification and practicing the invention disclosed herein. The present invention is intended to cover any variations, uses, or adaptations of the present invention that follow the general principles of the present invention and include common knowledge or customary techniques in the art not disclosed herein. The present invention is not limited to the precise structure described above and illustrated in the accompanying drawings, and various modifications and variations may be made without departing from the scope thereof. The scope of the present invention is limited solely by the appended claims.
Claims
1. A battery cell, characterized in that: The invention comprises a positive electrode sheet, a separator and a negative electrode sheet arranged in a stacked manner; the positive electrode sheet comprises a positive electrode active layer, the positive electrode active layer comprises single crystal particles of a ternary active material and polycrystalline particles of a ternary active material; the separator comprises a separator substrate and a lithium replenishing layer, the lithium replenishing layer is arranged on at least a portion of the surface of the separator substrate facing the positive electrode sheet; the lithium replenishing layer forms pores after the first formation; the battery cell satisfies formula 1, 0.5r≤v≤2R Formula 1 In Formula 1, v is the pore size, μm; r is the average particle size of the single crystal particles of the ternary active material, μm; and R is the average particle size of the polycrystalline particles of the ternary active material, μm.
2. The battery cell according to claim 1, characterized in that The negative electrode sheet includes a negative electrode active layer, and the negative electrode active layer includes a silicon-carbon material.
3. The battery cell according to claim 2, characterized in that The battery cell satisfies formula 2, X= a×54+b×5 Formula 2 In Formula 2, a is the silicon content in the negative electrode active layer, %; b is the carbon content in the negative electrode active layer, %; and X is the thickness of the lithium replenishing layer, μm.
4. The battery cell according to claim 3, characterized in that 5%≤a≤50%; and / or, 40%≤b≤80%; and / or, 5≤X≤30μm.
5. The battery cell according to any one of claims 1 to 4, characterized in that: The average particle size of the single crystal particles of the ternary active material is 2 to 5 μm; and / or the average particle size of the polycrystalline particles of the ternary active material is 6 to 15 μm.
6. The battery cell according to any one of claims 1 to 4, characterized in that: The lithium replenishing layer includes an organic lithium replenishing agent and a conductive agent, and the conductive agent includes carbon nanotubes; Preferably, the lithium replenishing layer comprises 70-80 parts of an organic lithium replenishing agent, 15-20 parts of a conductive agent, and 5-10 parts of a binder, in parts by weight.
7. The battery cell according to claim 6, characterized in that The organic lithium supplement comprises at least one of lithium squarate, lithium oxalate, lithium acetate, and lithium benzoate; And / or, the conductive agent further comprises carbon black; wherein the mass ratio of the carbon nanotubes to the carbon black is (10-20):(1-5).
8. The battery cell according to claim 6, characterized in that: The aspect ratio of the carbon nanotubes is 1000 to 10000; And / or, the carbon nanotubes and the organic lithium supplement agent satisfy Formula 3, 2C≤L≤16C Formula 3 In Formula 3, L is the length of the carbon nanotube, μm; C is the D50 of the organic lithium supplement, μm.
9. The battery cell according to any one of claims 1 to 4, characterized in that: The positive electrode sheet, the separator and the negative electrode sheet are sequentially stacked and wound to form an arc region and plane regions on both sides of the arc region. The lithium replenishing layer is provided on the surface of the separator substrate corresponding to the plane region. Preferably, the surface of the diaphragm substrate corresponding to the plane area includes N blank areas and M coating areas, and the lithium replenishing layer is provided in the coating areas; wherein N≥1 and M≥1.
10. A secondary battery, characterized in that: The battery cell comprises the battery cell according to any one of claims 1 to 9.